2017
DOI: 10.1108/jmd-05-2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and career advancement of female academic staff in Nigerian universities

Abstract: Purpose-The purpose of this paper is to examine the social capital factors of career advancement of female academic staff in Nigerian universities. Design/methodology/approach-A measurement and structural analysis were conducted for the three independent variables and a dependent variable on 20 public universities. Data were collected using a structured self-administered questionnaire. The dependent variable was female academic staff career advancement and the independent variables were mentoring, networking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
(75 reference statements)
2
9
0
Order By: Relevance
“…Summary statistics and correlations were delineated in Table II. Consistent with the works of Etehadi and Karatepe (2018), Hassan et al (2017) and Yao et al (2019), we used one-tailed test for the assessment of the correlations and hypothesized relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Summary statistics and correlations were delineated in Table II. Consistent with the works of Etehadi and Karatepe (2018), Hassan et al (2017) and Yao et al (2019), we used one-tailed test for the assessment of the correlations and hypothesized relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are many studies on the networking method in the field of leadership development (e.g. Chen et al, 2006;Hassan et al, 2017;Kodama, 2005;Lorange and Thomas, 2016;Pinto and Araújo, 2016), no research has explored or examined the quality of the networking and its influence on effective leadership development, given that networking involves the interaction of groups of employees, supervisors, managers and executives who do not have the same knowledge, experience or/ and qualifications.…”
Section: Networkingmentioning
confidence: 99%
“…The consensus based on the works of the abovementioned scholars is that young academic staff just entering the university system face many challenges and that if not properly guided they may be unable to successfully overcome them at the appropriate time. In a study by Hassan, Baharom & Mutalib (2017) on female academic staff in Nigerian universities, it was observed that the academic environment is fraught with many pitfalls for the unwary new entrant and at the same time, it holds many opportunities for growth and advancement that new academic staff may not be knowledgeable enough to take advantage of quickly. The role of mentoring therefore is to help the protégé avoid the dangers inherent in lecturing and harness the positive potentials to ensure a rewarding academic career (Ekechukwu & Horsfall, 2015).…”
Section: Need For Mentoring Amongst Nigerian Academicsmentioning
confidence: 99%